From ‘Forbidden Death’ to ‘Spectacular Death’ – on the transformation of death in the West (and maybe elsewhere) - Jacobsen , Michael Hviid (Studia Krytyczne/Critical Studies, 2024)
This article aspires to capture the contemporary ‘death mentality’ in the Western world by proposing a transition from the time of ‘Forbidden Death’ to the age of ‘Spectacular Death’. Whereas ‘Forbidden Death’ – which according to the originator of the concept, French historian Philippe Ariès – was characterized by a modern tabooing, denial and seques- tration of death, towards the end of the 20th century we began to witness the contours of a postmodern ‘revival of death’ tendency. In the wake of this, it is suggested that we now no longer live in a time of ‘Forbidden Death’, but rather live and die in an era of ‘Spec- tacular Death’ in which death has become a spectacle – something mostly to be observed from afar, but with an intense force of attraction. ‘Spectacular Death’ indicates that our collective experience of, attitude towards, relationship with and management of death is increasingly characterized by the following five main features: mediation/mediatization, commercialization, re-ritualization and palliative care humanization of death and dying and finally also an academic specialization in the study of death. The article ends with a brief critical discussion of the range, scope and analytical applicability of the notion of ‘Spectacular Death’ also outside a Western context.